A Feasiblity study on Euginthol Pastille - Alandy-Dy, Brian R.; Catbagan, Jennifer P.; Domingo, Rowena G.; Garcia, Florimae B. (College of Engineering, 1998)
Euginthol Pastilles, which is gong to be produced by B&B Corporation, is an effective sore throat medication which could also be used as a confectionery. Its main ingredients are Eucheuma, ginger and menthol crystals, thus the name Eu-gin-thol. The product is unique because of its Eucheuma seaweed content. It will be sold at a price 20% lower than its cheapest competitor based on its lower manufacturing cost and profit margin. Based on the market study, Euginthol can capture a market share of about 22.6% for 1999, 22.0% for 2000, 21.1% for 2001, 20.4% for 2002, and 19.8% for 2003. This market share was used as a basis for the product sales plan which amounts to 105,523,711.8g in 1999, 104,006,339.3g in 2000, 102,488,966.8g in 2001, 100,971,593.9g in 2002 and 99,476,823.6g in 2003. To effectively penetrate, compete and grow in the market, B&B Corporation will use an aggressive and competitive marketing strategy. The market strategy will utilize various media such as television and print advertisements as well as product sampling and promotional materials in drugstores and supermarkets. There will also be a two-level marketing channel of distribution, to ensure that the product is readily available to target users. The marketing budget for the first year will amount to Php 1,540,210.00. The project was also determined to be technically feasible. Manpower, raw materials and the different types of equipment are available and are sourced locally. Based on aggregate planning, the production of Euginthol will be constant per month, requiring four batches and two work-shifts per day. Through capacity planning and manpower allocation scheduling, a total of nineteen (19)production and packaging workers are required and a total of 26 major equipment is need Based on the facilities space requirements, the plant of b&B Corporation will be located at #162 E.Mariano St., Brgy. Dela Paz, Pasig City. The first year total project cost amounts to Php 75,265,810.00. To be able to finance the project, the company will need to loan an amount equal to Php26,391,023.65 from Metrobank and PhP 17,594,015.77 from investors. Based on the proforma financial statements, B&B Corporation will have an average net income of PhP 18,781,018.45 and will have a positive net cash-flow in the first year of operations. The project's payback period was also calculated to be 3.628 years and has a net present value (NPV) of phP 2,881,704.80. The rate of return (IRR) is 23%, based on the minimum attractive rate of return equal to 20%. Therefore, based on results, B&B Corporation is financially feasible and will be stable for the duration of the five-year study period. The organizational and management study showed that a corporate form of business is most beneficial to the project. The organizational structure composed of 19 direct and 13 indirect laborers, is expected to perform and accomplish its functions at an optimum level of efficiency. For the social profitability analysis, the project can bring considerable benefits to the society such as creation of about 32 new employees, government revenues from income taxes equal to an average of PhP 7,528,045.00 and withholding taxes amounting to PhP223,735.38 and significant contribution to the seaweed, sugar and chemical industries. Having evaluated and analyzed all the data and information regarding the project, the product "Euginthol Pastilles" by B&B Corporation is feasible. An appropriate proposal can therefore be prepared to further pursue the project.